2011
DOI: 10.1007/s00787-011-0213-1
|View full text |Cite
|
Sign up to set email alerts
|

Deliberate self-harm behaviors in Chinese adolescents and young adults

Abstract: The aim of this paper was to describe the prevalence of deliberate self-harm (DSH) and to determine the socio-demographic, behavioral, and psychological correlates of DSH behaviors in Chinese adolescents and young adults in a representative sample of the general population. The data were obtained from an epidemiologic study involving adolescents and young adults from junior and senior schools and colleges located in eight provinces of China. A total of 17,622 cases were retained for analysis. The relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 28 publications
8
79
2
Order By: Relevance
“…Overall, 20.4% of participants showed at least one incidence of NSSI in the past year, with girls being more likely than boys to engage in NSSI. These results are comparable with earlier studies with Chinese community adolescents (Wan, Hu, Hao, Sun, & Tao, 2011;You, Leung, & Fu, 2012;You, Leung, Fu, & Lai, 2011). Close examination of gender differences in the prevalence of each specific NSSI behavior revealed that girls were more likely to conduct self-cutting, carving, scratching skin, and biting, and boys were more likely to drip acid onto skin and scrub skin using bleach or cleaner.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, 20.4% of participants showed at least one incidence of NSSI in the past year, with girls being more likely than boys to engage in NSSI. These results are comparable with earlier studies with Chinese community adolescents (Wan, Hu, Hao, Sun, & Tao, 2011;You, Leung, & Fu, 2012;You, Leung, Fu, & Lai, 2011). Close examination of gender differences in the prevalence of each specific NSSI behavior revealed that girls were more likely to conduct self-cutting, carving, scratching skin, and biting, and boys were more likely to drip acid onto skin and scrub skin using bleach or cleaner.…”
Section: Discussionsupporting
confidence: 92%
“…However, where multivariate analysis was performed in two Indian studies, only null associations were found for value of livestock and value of agricultural produce amongst farmers 61 and for monthly household income. 56 Of the eleven studies on non-fatal SIB, six 35,41,42,48,57,65 using bivariate analysis reported a positive association and four 37,55,57,58 a null association. However, all studies 34,37,38,41,48,57,64 performing multivariate analysis found a positive association except one 34 which found a null association between perceived financial status and suicide attempts in China.…”
Section: Economic Status and Wealthmentioning
confidence: 98%
“…We assessed 29 (78%) studies to be of high [30][31][32][33][34][35][36][37][38][39][40][41][42][43] or acceptable [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] quality (Table 3). Eight studies [59][60][61][62][63][64][65][66] were of low quality due to problems with risk of bias: performance, attrition and detection bias (interrupted-time series); selection bias, unclear case definitions, detection bias, lack of adjustment for confounding factors (case-control studies); detection bias, lack of adjustment for confounding factors (cross sectional and ecological studies).…”
Section: <Figure 1> <Table 2>mentioning
confidence: 99%
“…Methods of self-harm include drug overdose, self-hitting, pinching, scratching, biting, self-cutting, burning, jumping from a high place, or self-poisoning (Yip, Ngan, & Lam, 2003 ). A study involving a large sample of adolescents in China (Wan, Hu, Hao, Sun, & Tao, 2011 ) showed that 17.0 % had harmed themselves in the past 12 months. The most common form of self-harm is self-hitting.…”
Section: Introductionmentioning
confidence: 99%